2018
DOI: 10.1038/s41598-018-29927-0
|View full text |Cite
|
Sign up to set email alerts
|

Stability of graph theoretical measures in structural brain networks in Alzheimer’s disease

Abstract: Graph analysis has become a popular approach to study structural brain networks in neurodegenerative disorders such as Alzheimer’s disease (AD). However, reported results across similar studies are often not consistent. In this paper we investigated the stability of the graph analysis measures clustering, path length, global efficiency and transitivity in a cohort of AD (N = 293) and control subjects (N = 293). More specifically, we studied the effect that group size and composition, choice of neuroanatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…Recent studies show that consistent results on graph metrics measured using cortical features and weighted network metrics can be achieved with fewer number of subjects in AD and control groups [38]. Thus, our study is more concerned about the use of graph theoretical analysis technique that generates stable results.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies show that consistent results on graph metrics measured using cortical features and weighted network metrics can be achieved with fewer number of subjects in AD and control groups [38]. Thus, our study is more concerned about the use of graph theoretical analysis technique that generates stable results.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, lower clustering coefficient values in SCD indicated a more randomly organized GMN suggesting a rapid decline in overall cognitive performance especially in the language (Verfaillie et al 2018b). Decreased values of path length and clustering coefficient have also been related with a subsequent future impairment in language, which is usually deteriorated in AD, as longitudinal studies have shown (Brier et al 2014;Tijms et al 2014;Mårtensson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed reduced local and global efficiency and degree centrality. A decreased local (Zhou and Lui, 2013) and global (Martensson et al, 2018) efficiency is a common characteristic of patients with AD. In addition, Aβ mouse model of amyloidosis (5XFAD mice) also showed a decreased network efficiency (Kesler et al, 2018).…”
Section: Discussionmentioning
confidence: 99%